The Sound of Others: Surprising Evidence of Conformist Behavior - Paolo Crosetto; Antonio Filippin (Institute for the Study of Labor (IZA), 2015)
It has been shown that subjects tend to follow others' behavior even when the external signals are uninformative. In this paper we go one step further, showing that conformism occurs even when the choices of others are not even presented to the subjects, but just indirectly perceived. We use the "Click" version of the Bomb Risk Elicitation Task, in which subjects can infer the behavior of others only from the mass of clicks heard. This signal is payoff-irrelevant and largely uninformative about the actual choices of the other participants. Moreover, it is never mentioned in the instructions and therefore it must be spontaneously (and possibly unconsciously) perceived in order to be used. We control the exposure of subjects to clicks by implementing treatments with and without earmuffs. Moreover, we test whether the introduction of a minimal form of commonality, i.e., facing a common rather than individual resolution of uncertainty, makes conformism more likely to emerge. We find strong evidence of conformist behavior even in such an adverse environment. Simply hearing the others clicking affects subjects' behavior. Introducing a common random draw results in a further dramatic shift of the average choices, in particular by women.
Keywords: C81; C91; D81; 330; conformism; risk attitude; experiment